Management of Patients with Concomitant Somatosensory Tinnitus and Temporomandibular Disorder: A Case Series - S Mahmoudian; S Farhadi; M Hosseinzadeh (Islamic Azad University, 2023)
Background and Aim: Multiple studies have shown the common co-occurrence of tinnitus and temporomandibular disorders (TMDs). This study assessed the effectiveness of a conservative treatment for TMD signs and symptoms of six patients with tinnitus-related complaints.    Materials and Methods: Six patients with persistent non-pulsatile tinnitus were evaluated in this case series. The tinnitus characteristics evaluated included pitch and loudness matching (PMT-LMT), minimum masking level (MML), and residual inhibition (RI). In addition, the Persian versions of the 52-item Tinnitus Questionnaire (TQ), the Tinnitus Handicap Inventory (THI), and the Steigerwald/Maher TMD Disability Index (SMTDI) were used. The corresponding TMD treatment plan was subsequently implemented, taking into account the subtype of the disease. The data were statistically analyzed at 0.05 level of significance. Results: The mean SMTDI score significantly decreased after treatment (P=0.0001) and the symptoms of TMD effectively resolved. Comparison of visual analog scale (VAS) scores of tinnitus patients before and after TMD therapy indicated statistically significant changes (P<0.05) in intensity, irritation, and awareness. Comparison of the mean tinnitus evaluation test scores before and after TMD therapy in tinnitus patients indicated a significant change only in PMT (P=0.039). Comparison of THI and TQ scores before and after TMD therapy revealed significant changes in tinnitus patients (P<0.05). Conclusion: In case of correct selection of patients with concurrent somatosensory tinnitus and TMD signs and symptoms, TMD therapy might alleviate this condition, according to the present findings. Consequently, a multidisciplinary approach may be useful in treatment of such cases.